Pro OpenGL ES for iOS - Smithwick, Mike (Apress : Imprint: Apress, 2011)
In Pro OpenGL ES for iOS, you'll find out how to harness the full power of OpenGL ES, and design your own 3D applications by building a fully-functional 3D solar system model using Open GL ES! OpenGL has set the standard for 3D computer graphics, and is an essential aspect of iPhone, iPad, and iOS development. This book offers everything you need to know, from basic mathematical concepts to advanced coding techniques. You'll learn by building this fascinating 3D solar system simulator! After introducing OpenGL ES, Pro OpenGL ES for iOS explains the basics of 3D math and then orients you to the iOS-native 3D libraries you'll be using in your own 3D games and the solar system project you'll build using this book. Through the solar system example project, you'll learn how to incorporate a variety of graphic and animation techniques into your applications. You will also discover how the full spectrum of 3D development that awaits, with topics such as lighting, texture-mapping, modeling, shaders, blending modes, and several more advanced concepts. By the time you finish Pro OpenGL ES for iOS, you'll have learned all the skills you'll need to build your own incredible 3D applications, based on one of the most powerful 3D libraries available.